Intervensi Kemanusiaan dalam Upaya Penanganan Isu Pelanggaran HAM Penduduk Kashmir Pasca Pencabutan Hak Otonomi Khusus Wilayah - Lina Nur Khofifah; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The revocation of Article 370 regarding the Special Autonomy Rights for the Kashmir Region which was controlled by India on August 5, 2019 then had a terrible impact, namely human rights violations against the Kashmiri population. India's revocation of Article 370 is the right step to fix various problems in the region and convince the world that the Kashmir issue is a purely Indian domestic problem that does not need to be interfered with by any party. However, Pakistan felt this move was arbitrary, until Pakistan showed a firm reaction through diplomatic and military options. To find out whether Pakistan's actions can be considered as acts of humanitarian intervention, this study seeks to answer them using one of the theories in the Three Grotian Theories, namely Fiduciary Theory. The use of this theory is used to see Pakistan's efforts in its efforts to carry out humanitarian intervention from diplomatic options to gather support and permission from the UN Security Council, as well as the possibility of its implementation through military options while meeting the demands of the Kashmiri insurgents with a focus on upholding human rights in Kashmir which has been seized by India.